2020
DOI: 10.1155/2020/6090262
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow Alterations in High Myopia: An Arterial Spin Labeling Study

Abstract: Objective. The aim of this study was to explore cerebral blood flow (CBF) alterations in subjects with high myopia (HM) using three-dimensional pseudocontinuous arterial spin labeling (3D-pcASL). Methods. A total of sixteen patients with bilateral HM and sixteen age- and sex-matched healthy controls (HCs) were recruited. All subjects were right-handed. Image data preprocessing was performed using SPM8 and the DPABI toolbox. Clinical parameters were acquired in the HM group. Two-sample t-tests and Pearson corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…Previous studies (23,24) have demonstrated that vision impairment causes reductions in cerebral BF, as well as functional changes, especially in vision-related areas such as the TL and occipital lobe (OL). However, other studies (25,26) have found increased CBF in visually impaired patients. In our research, the RCP BF had a positive correlation with TL and OL BF at both PLDs.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies (23,24) have demonstrated that vision impairment causes reductions in cerebral BF, as well as functional changes, especially in vision-related areas such as the TL and occipital lobe (OL). However, other studies (25,26) have found increased CBF in visually impaired patients. In our research, the RCP BF had a positive correlation with TL and OL BF at both PLDs.…”
Section: Discussionmentioning
confidence: 81%
“…The CBF maps were calculated from the ASL difference images and the reference images using a single-compartment model. The calculation process of CBF has been specifically described in a previous study ( Wang et al, 2020 ). First, the one-step registration method was used to spatially normalize the CBF map of each participant to a PET template in the Montreal Neurological Institute (MNI) space.…”
Section: Methodsmentioning
confidence: 99%
“…Arterial spin labeling (ASL) perfusion magnetic resonance imaging (MRI) is a noninvasive imaging modality that uses magnetically labeled blood water as an endogenous tracer to estimate tissue perfusion. 14 ASL allows the quantification of tissue microvascular blood perfusion and provides a large field of view with no depth limitations. 11 Compared to other ASL imaging techniques, such as continuous ASL (cASL) and pulsed ASL (pASL), the pseudocontinuous ASL (pcASL) technique has improved labeling efficiency and a superior intrasubject signal-to-noise ratio (SNR) 14 and is currently recommended clinically.…”
mentioning
confidence: 99%
“…Arterial spin labeling (ASL) perfusion magnetic resonance imaging (MRI) is a noninvasive imaging modality that uses magnetically labeled blood water as an endogenous tracer to estimate tissue perfusion 14 . ASL allows the quantification of tissue microvascular blood perfusion and provides a large field of view with no depth limitations 11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation